2009
DOI: 10.1111/j.1468-5906.2009.01441.x
|View full text |Cite
|
Sign up to set email alerts
|

A Power‐Control Theory of Gender and Religiosity

Abstract: The fact that women are more religious than men is one of the most consistent findings in the sociology of religion. Miller and Stark (2002) propose that a gender difference in riskpreference of physiological origin might explain this phenomenon. While acknowledging the utility of their risk-preference mechanism, we believe that their assumption regarding the genesis of this difference is a premature concession to biology. Returning to Miller's original paper on gender, risk, and religiosity (Miller and Hoffma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
130
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(141 citation statements)
references
References 67 publications
5
130
2
4
Order By: Relevance
“…Various theories have been used to explain gender differences in religiosity: for example, biology-based risk preferences (Miller and Stark 2002;Stark 2002), socialization-based risk preferences (Collett and Lizardo 2009), vulnerability (Norris and Inglehart 2011;Walter and Davie 1998), psychology (Beit-hallahmi 1997;Francis 1997;Freese and Montgomery 2007;Thompson 1991), and social structure and status (Luckmann 1967;de Vaus and McAllister 1987). The key question, however, has been whether the differences are universal or contingent on social context.…”
Section: Social Location and Status In A Gendered Institutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various theories have been used to explain gender differences in religiosity: for example, biology-based risk preferences (Miller and Stark 2002;Stark 2002), socialization-based risk preferences (Collett and Lizardo 2009), vulnerability (Norris and Inglehart 2011;Walter and Davie 1998), psychology (Beit-hallahmi 1997;Francis 1997;Freese and Montgomery 2007;Thompson 1991), and social structure and status (Luckmann 1967;de Vaus and McAllister 1987). The key question, however, has been whether the differences are universal or contingent on social context.…”
Section: Social Location and Status In A Gendered Institutionmentioning
confidence: 99%
“…Therefore, this article explores how gender differences vary by level of earned income-a gendered social location tied to status and social experiences-to consider not just how women and men differ but also how women differ from women and how men differ from men. Extending previous social location and class arguments (Chadwick and Garrett 1995;Collett and Lizardo 2009;hertel 1988;Luckmann 1967;de Vaus and McAllister 1987), this study examines whether gender differences are attenuated among elite earners. By focusing on and comparing elites, I answer the call by hastings and Lindsay (2013) to test whether nationally representative data validates their expectation that gender differences in religiosity are smaller among American elites.…”
mentioning
confidence: 99%
“…Similarly, some research on gender and religion has begun to suggest that gaps are not universal, with studies finding smaller gaps among high earners (Hastings and Lindsay 2013;Schnabel 2016), liberals (Baker and Whitehead 2016), and those raised in less patriarchal households (Collett and Lizardo 2009). Some research has even suggested that the size of gender gaps will vary by religious group, with the largest and most consistent gaps among Christians (Hackett et al 2016;Schnabel 2015a).…”
Section: Religions As Differently Gendered Institutionsmentioning
confidence: 99%
“…Women tend to be more religious than men in the U.S. and in many places around the world (Baker and Whitehead 2016;Collett and Lizardo 2009;Freese and Montgomery 2007;Roth and Kroll 2007;Schnabel 2016;Sullins 2006). For example, they tend to say religion is more important in their lives, pray more often, and attend religious services more frequently.…”
mentioning
confidence: 99%
“…Moreover, these women had possibly been exposed to gender egalitarian practices in the home, too, as they grew up. Collett and Lizardo (2009) argue, from their research on socialisation practices, that the religiosity gap among brothers and sisters more likely to be exposed to gender egalitarian values and socialisation practices while growing up is smaller than that which exists among those more likely to have been raised according to more traditional gender scripts. Their research also demonstrates that the effect of having been exposed to genderegalitarian values narrows the gender gap by rendering women exposed to these values less religious than other women and closer to men in their religious behaviour and beliefs.…”
Section: Similarities and Differencesmentioning
confidence: 99%